Spectral modification of type ia fibre bragg gratings by high-power near-infrared lasers - Kalli, Kyriacos; Simpson, Alexander George; Zhou, Kaiming; Zhang, Lin; Birkin, David J L; Ellingham, Tim J.; Bennion, Ian (My University, 2006)
We report the first experimental measurements on the spectral modification of type IA fibre Bragg gratings, incorporated in an optical network, which result from the use of high-power, near-infrared lasers. The fibre grating properties are modified in a controlled manner by exploiting the characteristics of the inherent 1400 nm absorption band of the optical fibre, which grows in strength during the type IA grating inscription. If the fibre network is illuminated with a high-power laser, having an emission wavelength coincident with the absorption band, the type IA centre wavelength and chirp can be modified. Furthermore, partial grating erasure is demonstrated. This has serious implications when using type IA gratings in an optical network, as their spectrum can be modified using purely optical methods (no external heating source acts on the fibre), and to their long-term stability as the grating is shown to decay. Conversely, suitably stabilized gratings can be spectrally tailored, for tuning fibre lasers or edge filter modification in sensing applications, by purely optical means.
Keywords: Bragg gratings; Optical fibers; Infrared radiation; Light absorption